Perancangan Website dan Sistem Informasi di Gereja Katolik Santo Paskalis Baylon Wangon Menggunakan Framework Laravel - Nugroho, Ignatius Dion; Prasetyo, Sri Yulianto Joko (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
The church is one that needs an information system to make it easier to convey information in the church every day. Therefore, the Catholic Church of St. Paskalis Baylon Wangon needs a website to convey all information to the people and the outside community. Judging from the development of Indonesian society today, the use of the internet as a means of information to the public is a new method that should be developed. The design of this website is expected to help the church in conveying information effectively. This developed information system has features such as worship schedules, church announcements, photo and video documentation, and contact information. With these features, the congregation is facilitated in obtaining information about activities in the church and worship schedules. This website can be accessed by congregants and church administrators as outside admins. This design uses the waterfall method, to design websites using the Laravel framework and using PHP and JavaScript programming languages.